Implementation of the Prohibition on Withholding Diplomas and Personal Documents by Companies in Indonesia - Fadli Januaris (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to analyze the implementation of the Circular Letter of the Minister of Manpower No. M/5/HK.04.00/V/2025 concerning the prohibition on withholding diplomas and personal documents by companies, focusing on its implications for the protection of workers’ rights and industrial relations in Indonesia. The research employs a juridical-empirical approach, combining a normative review of labor regulations with empirical data gathered through in-depth interviews and field observations in both formal and informal sector companies. The findings show that the policy strengthens the legal basis to prevent document retention practices, which have often been used as a form of control over workers. However, its implementation still faces challenges, including employer resistance, limited managerial understanding of the regulation, weak government supervision, and low worker awareness of their rights. These issues indicate that the effectiveness of the policy depends not only on legal provisions but also on stakeholder awareness and participation. The study concludes that the circular letter has strong potential to transform industrial relations toward a more balanced and trust-based partnership. Nevertheless, this requires continuous policy dissemination, improved enforcement mechanisms, and stronger involvement of labor unions. The academic contribution of this study lies in providing a comprehensive understanding of the interaction between labor regulation and industrial practices, while offering strategic recommendations to enhance the implementation of similar policies in the future. Keywords: Penahanan Ijazah, Menteri Ketenagakerjaan, Perlindungan Pekerja